2019
DOI: 10.1002/cdq.12179
|View full text |Cite
|
Sign up to set email alerts
|

Situational Interest and Scientific Self‐Efficacy: Influence of an Energy Science Career Intervention

Abstract: This study examined the efficacy of a career intervention aimed at promoting adolescents’ perceptions of scientific self‐efficacy (SSE), as well as interest in specific activities and careers relevant to energy science. One hundred thirty‐four adolescents (60 girls, 74 boys) completed self‐efficacy and interest measures on 4 occasions (Time [T] T1 to T4]) during the course of the 6‐day intervention. Results of latent change modeling yielded evidence of significant growth in SSE from T1 to T4. Results of a mult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…Dabney et al (2012) observed a strong relationship between professional interest in Science, Technology, Engineering and Mathematics (STEM) and participation in extracurricular scientific events since they can influence students' interest in scientific careers (Aubusson et al, 2012), or in scientific activities outside school hours. The importance of mastery experiences in promoting science, technology, engineering, and mathematics related careers has also been highlighted (Deemer & Sharma, 2019).…”
Section: Practical Implicationsmentioning
confidence: 99%
“…Dabney et al (2012) observed a strong relationship between professional interest in Science, Technology, Engineering and Mathematics (STEM) and participation in extracurricular scientific events since they can influence students' interest in scientific careers (Aubusson et al, 2012), or in scientific activities outside school hours. The importance of mastery experiences in promoting science, technology, engineering, and mathematics related careers has also been highlighted (Deemer & Sharma, 2019).…”
Section: Practical Implicationsmentioning
confidence: 99%